2010
DOI: 10.1007/s10103-010-0796-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different application durations of ER:YAG laser on intrapulpal temperature change during debonding

Abstract: This study was done to determine the amount of lasing time required to remove ceramic brackets safely without causing intrapulpal damage by using Er:YAG laser with the scanning method. Part 1: 80 bovine mandibular incisors with ceramic brackets were randomly assigned into four groups of 20 as one control and three study groups. In the study groups, brackets were debonded after lasing for 3, 6, and 9 s, whereas debonding was performed without lasing in the control group. Shear bond strengths and ARI scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 19 publications
5
71
1
5
Order By: Relevance
“…8,15,19 As shown by Nalbantgil et al, 15 the temperature proportionally increased as a function of laser irradiation time. They reported that lasing via a scanning approach was the most effective and safest way to debond ceramic brackets without causing injury to pulpal tissues.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…8,15,19 As shown by Nalbantgil et al, 15 the temperature proportionally increased as a function of laser irradiation time. They reported that lasing via a scanning approach was the most effective and safest way to debond ceramic brackets without causing injury to pulpal tissues.…”
mentioning
confidence: 78%
“…In another study Dostalováa et al 17 used 1997 nm longitudinally diode pumped Tm:YAP laser for debonding monocrystalline and polycrystalline ceramic bracket and concluded that the temperature rise was safe in both bracket types. Nalbantgil et al 15,19 used Er:YAG laser for bracket removal and observed that temperature increases for all specimens were below the 5.5°C benchmark. Sarp et al 8 used 1070-nm ytterbium fiber laser and reported minimal intrapulpal temperature rise.…”
Section: Marci Et Almentioning
confidence: 98%
See 2 more Smart Citations
“…A newly developed, effective and safe method for debonding ceramic brackets is called the scanning method by the Er:YAG laser, which was described by Nalbantgil et al [10]. This method is performed by applying the Er:YAG laser beam on a ceramic bracket while moving the hand piece horizontally over the entire surface of the ceramic bracket with a specific scanning time, frequency and specific energy [2].…”
mentioning
confidence: 99%